(untitled) (Ibrahim Cardiac Medical Journal, 2016)
Symptomatic thoracic aortic aneurysms (TAA) are rare. A 70 year-old man was admitted with hoarseness of voice for the last six months. Postero-anterior chest X-ray showed left hilar enlargement. Computerised thorax tomography (CTT) images were taken and a saccular TAA 8 cm in diameter was found. In this paper, we aimed to show that TAA should be considered as a differential diagnosis of patients with hoarseness of voice and hilar enlargement. Ibrahim Cardiac Med J 2014; 4(2): 61-63